The History of Reading, Volume 3
XXI, 229 p.
Keywords: We inhabit a textually super-saturated and increasingly literate world. This volume encourages readers to consider the diverse methodologies used by historians of reading globally, and indicates how future research might take up the challenge of recording and interpreting the practices of readers in an increasingly digitized society.